Equatorial electrojet current density turbulent reduction - Vega, Matías de la (1993)
It was shown in a previous paper that turbulence reduces the equatorial electrojet current density at noontime. This problem is further analyzed by computing the turbulence level in the long wavelength region of the spectrum using Kraichnan's direct interaction approximation (DIA). The self-consistent equations for the electrojet current density and turbulence level are solved; the current density thus obtained fits in well with experimental data.